1978
DOI: 10.1111/j.1476-5381.1978.tb08465.x
|View full text |Cite
|
Sign up to set email alerts
|

H1‐ AND H2‐RECEPTORS IN THE SMOOTH MUSCLE OF THE RUMINANT STOMACH

Abstract: 1 The effects of histamine on the longitudinal and circular smooth muscle from the rumen and reticulum of the bovine stomach have been analyzed by the use of H1-and H2-receptor antagonists. 2 Histamine caused three different types of response of the smooth muscle preparations: a contraction, contraction followed by relaxation. and a relaxation. These responses were resistant to the effect of tetrodotoxin, atropine, combined treatment with a-and j3-adrenoceptor blocking agents, hexamethonium and also to guaneth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Some authors have re ported that histamine affects stomach motil ity [26,27], Gerner et al [27] have shown on studies of isolated guinea pig stomachs that the histamine-induced activity is mediated by H| receptors. After intravenous applica tion of histamine in cats, Biancani et al [23] demonstrated in vivo phasic contractions of the pylorus with only slight effects on the antrum and duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have re ported that histamine affects stomach motil ity [26,27], Gerner et al [27] have shown on studies of isolated guinea pig stomachs that the histamine-induced activity is mediated by H| receptors. After intravenous applica tion of histamine in cats, Biancani et al [23] demonstrated in vivo phasic contractions of the pylorus with only slight effects on the antrum and duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…Contraction of the stomach in response to histamine was known to occur via the H1 receptor in the guinea pig (13) and the cat (17). As for relaxation of the bovine forestomach in response to histamine, an Hz receptor was reported to be involved (14). Taken together, these results sug-gest that histamine causes contraction via the H 1 receptor in the stomach.…”
Section: Discussionmentioning
confidence: 83%
“…It has been reported that histamine caused the contraction of guinea pig (13) and bovine (14) gastric smooth muscles. In the present study histamine stimulated obviously tonic contraction of the muscle strips from the fundus.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of these receptor subtypes is not homogeneous. For example, in the bovine and rat isolated stomach, histamine contracts or relaxes these tissues through activation of H.-or H2-receptors, respectively (Ercan & Tuirker, 1977;Ohga & Taneike, 1978). Histamine receptors responsible for contraction of the isolated guinea-pig oesophagus are mainly of the H,-receptor type with H2-receptors having a negligible role (Fujinuma et al, 1985).…”
mentioning
confidence: 99%